Morbidity Profile of Out-Patients Attending a Primary Health Centre in Rural Puducherry, South India - Arti Gupta; Vinoth Chellaiyan; Ayush Lohiya; Rizwan SA; Ravi P Upadhyay; Palanivel C (Medsci Publications, 2014)
Background: Knowledge on distribution and burden of diseases in a community is essential for planning of public health services. In the absence of information on morbidity profile through community based surveys, facility based data provide a good alternative.The aim of this study was to describe the morbidity profile of patients attending the Primary Health Centre (PHC). Methods: A record based descriptive study was carried out in a rural PHC of Puducherry, South India. Information on age, sex, residence, new or old case and principal diagnosis were extracted from the outpatient registers for the period between January, 2011 and December, 2011.Only newly registered patients for the study year (2011) were included. Descriptive analysis was done. Results: A totalof 68,818 episodes of illnesses were treated. Adults (>15 years) constituted about 84%. Overall respiratory disorders (26.2%) and musculoskeletal disorders (26.0%) were the most common illnesses followed by circulatory disorders (10.9%), digestive disorders (9.5%) and external causes of morbidity (7.6%). Conclusion:This study gives a brief description of the morbidity profile of patients attending a primary health care centre over a period of one year. This knowledge would help in planning health services to meet the patients' needs and also help in training health staff.